A major natural genetic variation associated with root system architecture and plasticity improves waterlogging tolerance and yield in soybean. (16th April 2018) - Ye, Heng; Song, Li; Chen, Huatao; Valliyodan, Babu; Cheng, Peng; Ali, Liakat; Vuong, Tri; Wu, Chengjun; Orlowski, John; Buckley, Blair; Chen, Pengyin; Shannon, J. Grover; et al.
Abstract: Natural genetic variations in waterlogging tolerance are controlled by multiple genes mapped as quantitative trait loci (QTLs) in major crops, including soybean ( Glycine max L.). In this research, 2 novel QTLs associated with waterlogging tolerance were mapped from an elite/exotic soybean cross. The subsequent research was focused on a major QTL ( qWT_Gm03 ) with the tolerant allele from the exotic parent. This QTL was isolated into near‐isogenic backgrounds, and its effects on waterlogging tolerance were validated in multiple environments. Fine mapping narrowed qWT_Gm03 into a genomic region of <380 Kbp excluding Rps1 gene for Phytophthora sojae resistance. The tolerant allele of qWT_Gm03 promotes root growth under nonstress conditions and favourable root plasticity under waterlogging, resulting in improved waterlogging tolerance, yield, and drought tolerance‐related traits, possibly through more efficient water/nutrient uptakes. Meanwhile, involvement of auxin pathways was also identified in the regulation of waterlogging tolerance, as the genotypic differences of qWT_Gm03 in waterlogging tolerance and formation of adventitious/aerial roots can be complemented by an exogenous auxin‐biosynthesis inhibitor. These findings provided genetic resources to address the urgent demand of improving waterlogging tolerance in soybean and revealed the determinant roles of root architecture and plasticity in the plant adaptation to waterlogging. Abstract : A major natural genetic variation/QTL to improve waterlogging tolerance was identified from an exotic soybean line. The tolerant allele of this natural genetic variation showed better root growth and more favourable root plasticity to facilitate adequate water and nutrient uptake under nonstress and waterlogging stress conditions, possibly through auxin pathways. In addition to its role in waterlogging tolerance, the tolerant allele of this natural variation help improve yield and drought tolerance‐related traits possibly due to the better root growth.